2020
DOI: 10.1186/s40359-020-0373-1
|View full text |Cite
|
Sign up to set email alerts
|

Swipe-based dating applications use and its association with mental health outcomes: a cross-sectional study

Abstract: Background: Swipe-Based Dating Applications (SBDAs) function similarly to other social media and online dating platforms but have the unique feature of "swiping" the screen to either like or dislike another user's profile. There is a lack of research into the relationship between SBDAs and mental health outcomes. The aim of this study was to study whether adult SBDA users report higher levels of psychological distress, anxiety, depression, and lower self-esteem, compared to people who do not use SBDAs. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…This same age group accounts for 25% of the annual incidents related to mental diseases, out of which, 12% of incidents result in mental disorders and substance abuse. Individuals who used swipe-based dating apps on a regular basis and for more than a year were also shown to have slightly statistically higher rates of psychological anxiety and depression, which is comparable to a finding regarding people who used social media more often and for longer periods of time (Holtzhausen et al 2020). Within these data, Australian women and LGBTQI+ people displayed higher levels of psychiatric distress when compared to men, but not lower self-esteem.…”
Section: Online Datingsupporting
confidence: 49%
See 2 more Smart Citations
“…This same age group accounts for 25% of the annual incidents related to mental diseases, out of which, 12% of incidents result in mental disorders and substance abuse. Individuals who used swipe-based dating apps on a regular basis and for more than a year were also shown to have slightly statistically higher rates of psychological anxiety and depression, which is comparable to a finding regarding people who used social media more often and for longer periods of time (Holtzhausen et al 2020). Within these data, Australian women and LGBTQI+ people displayed higher levels of psychiatric distress when compared to men, but not lower self-esteem.…”
Section: Online Datingsupporting
confidence: 49%
“…At the start of the COVID-19 pandemic, Tinder reported 3 billion swipes in a single day. Tinder is a significant dating application; in 2018, there were 57 million users worldwide (Holtzhausen et al 2020). Currently, Tinder is the most downloaded dating service in the world, with over six million monthly users in January 2021 (Tankovska 2021a).…”
Section: Covid-19 and Its Implications For Intimate Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect of the shidduch system can be compared to the modern‐day use of dating websites where individuals decide whom to date based on resumes and photos. Indeed, research indicates that the use of dating websites such as Tinder and other swipe‐based dating applications is associated with increased depression, anxiety, distress, and body shame (Holtzhausen et al, 2020; Strubel & Petrie, 2017). While previous research highlights that the shidduch system, unlike the secular dating system, circumvents heartache by its intellectualized style dating ensuring that individuals marry based on shared values (Golker & Senior, 2021; Milevsky et al, 2011), this study indicates that many community members feel that the shidduch system has evolved in ways that no longer accomplishes that goal.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 In a study that included 437 Australian participants, higher depression, anxiety, and stress scores were found among users of Swipe-Based apps compared to participants who did not use them. 12 Another study, with 3074 participants, added that social anxiety symptoms were shown to be positively related to the use of these platforms, with these symptoms predicting a lower likelihood of initiating contact with a “match” in male but not female users. 13 It has been described that Tinder is positively related to reporting more sexual partners and non-consensual sexual intercourse, the last being more prevalent among women and sexual minorities.…”
Section: Introductionmentioning
confidence: 99%